IDENTIFIKASI TIPE-TIPE KERUSAKAN PADA BAHAN PAKAN BADAK DI TAMAN NASIONAL WAY KAMBAS (STUDI KASUS TEGAKAN POHON PADA AREA RESTORASI) - Lestari, Wulan Ayu; Safe'i, Rahmat; Dirgantara, Dirgantara (Lambung Mangkurat University-Indonesia, 2024)
The quality of rhinoceros feed can be seen based on the health condition of the stand. It is necessary to monitor the condition of tree damage to maintain the quality of rhinoceros feed. This study aims to identify the types of damage to vegetation as rhinoceros feed. This research method is based on the Forest Health Monitoring (FHM) technique with several stages, namely: observation of the research location; determination and creation of cluster plots; identification of damage and percentage of tree damage. The results of the study showed that, in the Rawa Kidang restoration and Bambangan restoration, the dominant damage locations were found on the branches and leaves. In addition, the dominant types of damage found were broken/dead branches and leaves and damaged shoots/buds, with percentage values in Rawa Kidang of 27.47% and 59.89%, respectively, while in Bambangan it was 50.50% and 25.89%. The causes of damage to branches include weather factors, pests, and plant diseases while the main causes of damage to leaves are weather, availability of nutrients, and disruption of the photosynthesis process. The presence of parasites and fungi that arise due to high humidity can attack the trunk and branches, so that these parts will rot and be easily damaged or broken if exposed to strong pressure, such as strong winds. Thus, the type of damage most often found in Rawa Kidang Restoration and Bambangan Restoration is damage to branches and leaves with a percentage interval of damage of 25–60%.